The Effect of Liquidity, Profitability, Leverage and Activity on Stock Return: The Case of Health Care Sector Firms Listed on Indonesia Stock Exchange - Hidayatullah, Rosyadi; Djazuli, Abid; Choiriyah, Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
The formulation of the problem in this study is the effect of liquidity, profitability, leverage, and activity on stock returns in Healthcare sector companies listed on the Indonesia Stock Exchange. The purpose of this study is to determine the effects of liquidity, profitability, leverage, and activity on stock returns of Healthcare sector companies listed on the Indonesia Stock Exchange. This type of research is associative. The population used in this study is companies listed in the Healthcare sector. The sample comprised 8 companies, using the Purposive sampling technique. The data used in this study are secondary. The data collection method used is through Documentation. The data analysis technique used is multiple linear regression. The results of this study indicate that liquidity, profitability, leverage, and activity simultaneously affect stock returns in Healthcare sector companies listed on the Indonesia Stock Exchange. The results of the study partially show that profitability has a significant effect on stock returns in Healthcare sector companies listed on the Indonesia Stock Exchange. The results of the determination coefficient show that the contribution of liquidity, profitability, leverage, and activity to stock returns is 23.8%